India and the United Kingdom—What big data health research can do for a country. Issue 2 (18th November 2018) - Bandopadhyay, Souvik; Murthy, Gudlavalleti Venkata Satyanarayana; Prabhakaran, Dorairaj; Taylor, Paul; Banerjee, Amitava
Abstract: Introduction: Big data and growth in telecommunications have increased the enormous promise of an informatics approach to health care. India and the United Kingdom are two countries facing these challenges of implementing learning health systems and big data health research. Analysis: At present, these opportunities are more likely to be exploited in the private sector or in public‐private partnerships (eg, Public Health Foundation of India [PHFI]) than public sector ventures alone. In both India and the United Kingdom, the importance of health informatics (HIs), a relatively new discipline, is being recognised and there are national initiatives in academic and health sectors to fill gaps in big data health research. The challenges are in many ways greater in India but outweighed by three potential benefits in health‐related scientific research: (a) increased productivity; (b) a learning health system with better use of data and better health outcomes; and (c) to fill workforce gaps in both research and practice. Conclusions: Despite several system‐level obstacles, in India, big data research in health care can improve the status quo, whether in terms of patient outcomes or scientific discovery. Collaboration between India and the United Kingdom in HI can result in mutual benefits to academic and health care delivery organisations in both countries and can serve as examples to other countries embracing the promises and the pitfalls of health care research in the digital era.